Respostas
respondido por:
0
Resposta:
A)
(-3*x)/8+y=-1;x)
=[(8+8*"y")/3]
=(8+8*"y")/3
B)
(3*x)/7-y=2;x)
=[-(-14-7*"y")/3]
=-(-14-7*"y")/3
Explicação passo-a-passo:
A)
(-3*x)/8+y=-1
x = (1+y)/(3/8)
x = (8+8*y)/3
solução da equação (-3*x)/8+y=-1 é [(8+8*y)/3]
B)
(3*x)/7-y=2
x = -(-2-y)/(3/7)
x = -(-14-7*y)/3
resultado= (3*x)/7-y=2 é [-(-14-7*y)/3]
espero que esteja certo
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás